Destructive or Deliberative? An Investigation of the Evolution, Determinants and Effects of the Quality of Political Debate: PhD by Ine Goovaerts (KU Leuven), supervisors: Sofie Marien and Anna Kern (Ghent University) - Bächtiger, André (Politics of the Low Countries, 2025)
The quality of public and political discourse has moved to the forefront of current debate and academic research in recent years. Indeed, the fact that we are currently experiencing a crisis of public communication (Dryzek et al., 2019) – including the rise in simplifying and disrespectful populist language – has turned high-quality argumentation and respectful listening not only into a desirable feature of well-functioning democracies but also into an ‘early warning sign’ when democracies are ‘backsliding’. Ine Goovaerts’ dissertation explores the question of reasonability and civility of political discourse both at a theoretical and at an empirical level.